The Influence of Promotion, Price, And Product Quality on Purchase Decision of Mild Cigarette Product - Dawanto, Muhammad Alief Fitrah (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2023)
This study aims to determine the effect of promotion, price, and product quality on purchase decision of mild cigaratte product (consumer study on Sampoerna A Mild in Malang City). This type of research was an explanatory research with quantitative methods. This study used a sample of 100 respondents and sampling used non-probability sampling techniques by using the purposive sampling method. The criteria required for respondents in this study are at least 18 years old, have or are currently consuming Sampoerna A Mild, and live in Malang City. Measurement of the value of question items in the questionnaire ussed a Likert scale with a score of 1-5. This study used the Statistical Package for the Social Sciences (SPSS) to conduct validity test, reliability test, and classical assumption test. Data analysis techniques applied multiple linear regression tests. Hypothesis test was also carried out to test hypotheses partially and dominantly. Based on the results of hypothesis testing, the variables of promotion (X1), price (X2), and product quality (X3) each has a partially and simultance significant effect on purchase decisions with product quality (X3) as the dominant influential variable.   Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh promosi, harga dan kualitas produk terhadap keputusan pembelian produk rokok mild (studi konsumen pada Sampoerna A Mild di Kota Malang). Jenis penelitian ini adalah explanatory research dengan metode kuantitatif. Penelitian ini menggunakan sampel sebanyak 100 responden, Pengambilan sampel menggunakan teknik non probability sampling dengan metode purposive sampling. Kriteria responden yang dibutuhkan dalam penelitian ini adalah berusia minimal 18 tahun, pernah atau sedang mengkonsumsi Sampoerna A Mild dan berdomisili di Kota Malang. Pengukuran nilai item pertanyaan dalam kuesioner menggunakan skala likert dengan skor 1-5. Penelitian ini menggunakan Statistical Package for the Social Sciences (SPSS) untuk melakukan uji validitas, uji reliabilitas dan uji asumsi klasik. Teknik analisis data menggunakan uji regresi linear berganda. Uji hipotesis dilakukan untuk menguji hipotesis secara parsial, simultan dan dominan. Berdasarkan hasil pengujian hipotesis diperoleh data variabel promosi (X1), harga (X2), dan kualitas produk (X3) masing-masing berpengaruh signifikan secara parsial dan simultan terhadap keputusan pembelian, dengan kualitas produk (X3) sebagai variabel yang berpengaruh dominan.